DESORPSI CAMPURAN Au(III) DAN Cu(II) DARI MAGNETIT TERLAPIS HIBRIDA MERKAPTO-SILIKA DENGAN LARUTAN TIOUREA DALAM ASAM KLORIDA - , ANI QOMARIYAH; , Prof. Dr. Nuryono, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Desorption of Au(III) and Cu(II) from mercapto-silica hybrid coated magnetite (M/MSH) with thiourea in hydrochloric acid solution has been studied. Magnetite was obtained through Fe3+/Fe2+ salt mixture co-precipitation using NH4OH as precipitating solution. Coating was done through the sol-gel process by mixing magnetite, sodium silicate (Na2SiO3) from rice husk ash and 3- mercaptopropyltrimethoxysilane (MPTMS) till pH of 7.0 (neutral) using HCl or NH4OH solution. M/MSH was characterized with Fourier Transform Infrared (FTIR) Spectrophotometry and X-Ray Diffraction (XRD) methods. Adsorption of metal ions was carried out in a batch system for 50 minutes on pH of 3.0. The adsorbed metal ions were quantitatively calculated based on the difference of metal concentration before and after adsorption analyzed using Atomic Absorption Spectrophotometer (AAS). The metal ions adsorbed on M/MSH adsorbent were desorbed using thiourea in HCl solution with variation of thiourea concentration and desorption time. Total desorption of metal ions was calculated based on the AAS analysis. The FTIR characterization results indicated that the success of M/MSH synthesis was shown with the presence of specific absorption of functional groups namely methylene group (-CH2-), thiols (-SH), silanol group (Si-OH), siloxan group (Si-O-Si) and magnetite Fe-O bonding. The XRD data showed that the structure of M/MSH was chrystalline-like. Kinetic study demonstrated that the desorption of Au(III) and Cu(II) in a single and biner system were pseudo-second order. The value of reaction rate constant (k) for Au(III) was higher than Cu(II). The mixture of 131 mg Au(III) and 14 mg Cu(II) adsorbed on 10 mg adsorbent can be desorbed optimally with 6% thiourea in HCl 0.1 M solution (88% for Au(III) and 56% for Cu(II)). The desorption selectivity of Au(III) toward Cu(II) gave a value of Î± = 3.1.